Enhancing cross border connectivity: venturing into Islamic finance as a new source of infrastructure financing / Saadiah Mohamad ... [et al.] - Mohamad, Saadiah; Salah, Omar; Mokhtar, Mafrukhin; Syed Alwi, Sharifah Faigah (Universiti Teknologi Mara Selangor, 2015)
Unlike the traditional Finance, Islamic finance must observe the teachings of Shari'ah whose basic teaching cannot be violated at any point in time. These basic teachings constitute the core element of the faiths that are best described as maqasid al-shari'ah. While prohibiting Riba, Gharar, Maysir, Islam promotes maslahah by protecting the interests and benefits of all parties involved in the market. This paper emphasizes on the main underlying causes ('Illah) for the prohibition of these on the basis of Islamic and socio-economic point of views. This is paper is based on secondary sources such as classical books, articles etc. There is no difference of opinion among scholars that Riba, Gharar, Maysir is clearly prohibited by both Quran and the Sunnah. However, Questions continue to be raised about their meanings and implications because of the diverse applications in commercial transactions (Mu'malat). This paper is a humble attempt to clarify the meaning and implications of these terms.